Decentralized Decision Intelligence Using AI and Blockchain in Modern Enterprises - Ayubi, M. Nizar; Anggoro, Sigit; Kareem, Yasir Mustafa (ADI Publisher, 2025)
In the era of digital transformation, enterprises face increasing pressure to enhance transparency, operational efficiency, and trust in their decision making processes, especially in complex, data-intensive environments. While prior studies have separately explored the roles of Artificial Intelligence (AI) and Blockchain, few have examined their combined impact in creating decentralized and intelligent decision systems within real enterprise contexts. This study introduces a novel conceptual integration model that merges AI-driven analytics with blockchain-based validation mechanisms to enable transparent, traceable, and autonomous decision-making. By synthesizing AI predictive and analytical capabilities with blockchain immutable and distributed architecture, this research extends recent studies (2021-2025) by demonstrating how such convergence can eliminate central dependencies, enhance digital trust, and support data governance across departments. A qualitative case study approach was used to analyze organizations adopting AI blockchain frameworks, and the findings reveal new insights on interoperability, adaptive governance, and smart contract-driven autonomy. The study originality lies in its emphasis on the AI Blockchain synergy as a unified decision-intelligence infrastructure, contributing to the growing discourse on ethical and resilient enterprise systems.